ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI ANGKA PARTISIPASI SEKOLAH SERTA ANGKA PUTUS SEKOLAH TINGKAT SEKOLAH DASAR DAN SEKOLAH MENENGAH PERTAMA: Data Panel 33 Provinsi di Indonesia Tahun 2006 Hingga 2011 - , NIKEN AJENG LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increased school enrollment rate (ER) and decreased school dropout rate (DR) for elementary and junior high school level (primary education), became one of the targets of the provincial government as stated in the medium-term development plan (RPJMD) of each province in Indonesia. This study aims to determine the factors that influence change in ER and DR at elementary and junior high school level. Four aspects were analysed to see whether they have influenced the change in ER and DR. Those aspect are the government, school, households, and regional characteristics. The data used in this study is a provincial-level panel data, which will be estimated by applying econometric approach. Of the four aspects above, variables that are expected to affect ER and DR described through literature study and previous researches. The results showed that not all of the aspects affecting change in ER and DR at this primary education level. However, the school aspect which described by the pupil teacher ratio and the number of schools, as well as the regional characteristic aspect apparently shows its significance to the ER and DR at all level. This result becomes important for the government in which either the construction of physical or the development non-physical provide a positive impact for the development on the education sector. Keyword: enrollment rate, drop-out rate, primary school, secondary school, province, panel data